Measurement of the 43Sc production cross-section with a deuteron beam. (March 2019) - Carzaniga, Tommaso Stefano; van der Meulen, Nicholas P.; Hasler, Roger; Kottler, Christian; Peier, Peter; Türler, Andreas; Vermeulen, Etienne; Vockenhuber, Christof; Braccini, Saverio
Abstract: 43, 44 Sc/ 47 Sc is one of the most promising theranostic pairs in nuclear medicine. The co-emission of 1157 keV γ -rays with 99.9% branching ratio by 44 Sc and the presence of its metastable state 44 m Sc push to favour the adoption of 43 Sc for Positron Emission Tomography (PET) diagnostic procedures to lighten the dose to the patient and to the personnel. The β + emitter 43 Sc can be produced at a medical cyclotron by proton bombardment of an enriched 43 Ca or 46 Ti oxide target. 43 Sc can be also produced by deuteron bombardment of an enriched 42 Ca oxide target. Only a few medical cyclotrons currently in operation offer deuteron beams. Some can be adapted to operate both a proton or a deuteron source. To compare these three production routes, an accurate knowledge of the cross-sections is essential. In this paper, we report on the cross-section measurement of the reaction 42 Ca(d, n) 43 Sc performed at the 6 MV HVEC EN-Tandem of the Ion Beam Physics group at ETH in Zürich. A study of the production yield by using commercially available enriched target materials is also presented. Abstract : Highlights: The production cross-section of the reaction 42Ca(d, n)43Sc was measured. Thick target yields and purities evaluated and compared with other production routes. Method based on irradiating the full target by constant surface density deuteron beam. Measurement performed up to 7.5 MeV with a tandem accelerator.